Reinterpretasi Pembagian Waris dalam Q.S. An-Nisa’ Ayat 11: Studi Analisis Hermeneutika Muhammad Syahrur - Khoiriyah, Inayah; Saerozi, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study examines the reinterpretation of the division of inheritance in Q.S. An-Nisa’ verse 11 using Muhammad Syahrur’s hermeneutical approach. The primary focus is on the part of the verse which states that if there are two or more daughters and no sons, they are entitled to two-thirds of the inheritance. Classical interpretations generally understand this verse literally. However, Muhammad Syahrur offers a markedly different perspective by applying his boundary-based hermeneutics (al-hudud). He interprets the provision not as a fixed amount but as a maximum limit, meaning that two-thirds is the upper boundary while one-third represents the lower boundary. Consequently, the distribution of inheritance becomes flexible and contextual, aligning with the evolving circumstances of modern times. This research aims to understand how Syahrur's approach offers a new perspective on Islamic inheritance law and to assess the compatibility of his views with the principles of gender justice and contemporary social developments. The method employed in this study is library research with a descriptive-qualitative approach. The findings reveal that Syahrur’s interpretation provides a more flexible understanding of Qur'anic verses. Through his boundary theory, Syahrur proposes a proportional distribution of inheritance between men and women. According to him, the